(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
New primary source material documents the expansion of Montgomery Ward’s mail order through their export department to Latin American consumers from the end of the Spanish American War in 1898 to ca.1930, and the formative period of export advertising and mail order marketing for the first time. Chicago was the center of mail order and ready-made clothing; women’s ready-made suits provide a case study of merchandise. A Chicago clothier requested a U.S. State Department inquiry to study the viability of introducing American ready-made clothing in Latin America in 1899. This Government study provides significant details about ready-made clothing in Latin America previously unknown to scholars. U.S. mail order required international parcel post for growth, and a Ward employee championed its passage in 1919. New primary sources have been contextualized within the frameworks of business, advertising, postal, and dress history and political economy. Advances in export advertising led to growth, which has been traced using statistics from trade journals and an internal document about the history of the export department. The essay ends by examining the names and addresses of Latin American consumers from extant Montgomery Ward return envelopes that have been digitally mapped and interpreted. Latin American consumption theory will be examined apropos of consumers and the meaning of mail order goods.